The Effect of Capital, Labor and Raw Materials Toward Production Value (Study on Tapioca Flour Industry in Margoyoso District, Pati Regency) - Putri, Berlian Aminanti Suraya; Dian Wisika Prajanti, Sucihatiningsih Dian Wisika Prajanti; Pujiati, Amin (Universitas Negeri Semarang, 2020)
Tapioca flour industry had a significant contribution toward the surrounding residents economy because it is able to absorb a significant amount of labor. This study aimed to determine the effect of capital, labor and raw materials toward the production of tapioca flour industry in Margoyoso District, Pati Regency. This study used the Ordinary Least Square (OLS) method, namely multiple linear regression analysis. The results of this study indicated that there wass a positive and significant influence of capital, labor and raw materials toward the value of tapioca flour production in Margoyoso District, Pati Regency. Capital had the most dominant influence on tapioca flour production.